AVRUPA BİRLİĞİ NORMLARI VE AİHM KARARLARI ÇERÇEVESİNDE KUZEY KIBRIS - Kudret Özersay (Ankara Avrupa Çalışmaları Dergisi)
ABSTRACTSubmission of the Annan Plan to the separate simultaneous referenda on the one hand and accession of the Greek Cypriot State to the European Union on behalf of the 1960 Republic of Cyprus on the other, have affected main parameters of the Cyprus conflict. 2003 Treaty of Accession defines the territory of the TRNC as “the areas of the Republic of Cyprus in which the government of the Republic of Cyprus does not exercise jurisdiction” and the ECHR has decided that this part of the Island was under the effective control of Turkey and this State should be responsible for human rights violations in these areas. This article aims to discuss and provide some legal ideas on reflections of recent political atmosphere on Turkey’s responsibility in the North and on possible future attitude of the ECHR to the cases originated from Cyprus conflicGİRİŞBir yandan, Kıbrıs sorununa kapsamlı bir çözüm bulunmasını hedefleyen ve Kasım 2002’de adadaki taraflara sunulan BM Planı, diğer yandan ise Kıbrıs Rum devletinin AB’ne tam üye olma süreci, Kıbrıs adasında çok farklı ve hızlı birtakım gelişmelerin yaşanmasına neden olmuştur.